PENGARUH ETOS KERJA DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) PEMATANGSIANTAR - Pradita, Pradita; Lie, Darwin; Efendi, Efendi; Inrawan, Ady (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
As for this research problem formula is how work ethics and job satisfaction on working discipline at Kantor Pelayanan Perbebndaharaan Negara (KPPN) Pematangsiantar. Research Method used in this writing is library research and field research. Its population and sample is employees Pelayanan Perbebndaharaan Negara (KPPN) Pematangsiantar  amount to 28 people. Considering responder amount less than 100 people to reply the questionnaires which writer propagate and availibility of writer time and also for the accuracy of result of research. In this study using  qualitative data and quantitative data, and technique of data collecting by questionnaires, interview and documentation. Then technique analyse the data use the descriptive method qualitative and quantitative descriptive method.Result of analysis from linear regresi modestly that is Ŷ=35,010 + 0,491X1 + 0,763X2 meaning there are positive influence work ethics and job satisfaction on working discipline at Kantor Pelayanan Perbebndaharaan Negara (KPPN) Pematangsiantar. The strength of relationship between the variables is very strength, that is r= 0,781. From coefficient determinasi can explainable high and low of customer’s purchase decision 61%, and the rest 39 % explained by other factor which is not discussed in this research. From result of processing and calculation questionnaires, writer get the conclusion that work ethics and job satisfaction applied by work ethics and job satisfaction on working discipline at Kantor Pelayanan Perbebndaharaan Negara (KPPN) Pematangsiantar.an effect on to working discipline. This matter is proved by hypothesis test either simultaneously where result test the fhitung (19,537) > ftabel (3,39) and which significant 0,000 < alpha 0,05. Keywords: Work Ethics, Job Satisfaction,Working Discipline